From Blood to Brain: Adult-Born Neurons in the Crayfish Brain Are the Progeny of Cells Generated by the Immune System - Beltz, Barbara S.; Benton, Jeanne L. (Frontiers in Neuroscience, 2017)
New neurons continue to be born and integrated into the brains of adult decapod crustaceans. Evidence in crayfish indicates that the 1st-generation neural precursors that generate these adult-born neurons originate in the immune system and travel to the neurogenic niche via the circulatory system. These precursors are attracted to the niche, become integrated amongst niche cells, and undergo mitosis within a few days; both daughters of this division migrate away from the niche toward the brain clusters where they will divide again and differentiate into neurons. In the crustacean brain, the rate of neuronal production is highly sensitive to serotonin (5-hydroxytryptamine, 5-HT) levels. These effects are lineage-dependent, as serotonin's influence is limited to late 2nd-generation neural precursors and their progeny. Experiments indicate that serotonin regulates adult neurogenesis in the crustacean brain by multiple mechanisms: via direct effects of serotonin released from brain neurons into the hemolymph or by local release onto target cells, or by indirect influences via a serotonin-mediated release of agents from other regions, such as hormones from the sinus gland and cytokines from hematopoietic tissues. Evidence in crayfish also indicates that serotonin mediates the attraction of neural precursors generated by the immune system to the neurogenic niche. Thus, studies in the crustacean brain have revealed multiple roles for this monoamine in adult neurogenesis, and identified several pathways by which serotonin influences the generation of new neurons.